High cyanobacterial nifH gene diversity in Arctic seawater and sea ice brine - Díez, Beatriz; Bergman, Birgitta; Pedrós-Alió, Carlos; Antó, Meritxell; Snoeijs, Pauline (Environmental Microbiology Reports, 2012)
7 pages, 3 figures Although cyanobacterial diazotrophs are common in Arctic terrestrial and freshwater habitats, they have been assumed to be absent from Arctic marine habitats. We report here a high diversity of cyanobacterial nifH genes in Fram Strait and the Greenland Sea. The nifH gene encodes the iron protein of the nitrogenase enzyme complex, which is essential for biological N2 fixation. Using primers specific for nifH genes we uncovered communities of autotrophic and heterotrophic bacteria in sea ice brine and seawater between latitudes 65 and 81°N. Cyanobacteria (Oscillatoriales and Chroococcales) with known marine planktonic and benthic distributions were distinguished, alongside a mix of metabolically versatile eubacteria (nifH Clusters I and III). Using primers selective for cyanobacterial nifH genes we identified filamentous non-heterocystous Trichodesmium-like and LPP (Leptolyngbya, Phormidium and Plectonema)-like Oscillatoriales, as well as Cyanothece-like Chroococcales in a brine sample from 81°N. The occurrence of Trichodesmium-like cyanobacteria was further confirmed by sequences of the hetR gene of Trichodesmium. Microscopic examinations confirmed the presence of viable filamentous and unicellular cyanobacteria. Our results reveal the potential for microbial N2 fixation in the Arctic seas. However, it is still left to determine if these genes are also metabolically active before any biogeochemical importance of diazotrophy in the polar oceans can be assessed This work was funded by the Swedish Research Council (VR) and the Swedish Polar Research Secretariat through participation of P.S. in the expedition ‘Arctic Ocean 2002’ with ice-breaker ‘Oden’, the K and A. Wallenberg Foundation, and the Swedish Foundation for International Cooperation in Research and Higher Education. We thank A. Anesio (University of Lund, Sweden) for the on-board bacterial cell counts Peer reviewed